AN ALTERNATIVE APPROACH TO SURGICAL TREATMENT FOR DIASTASIS OF RECTUS ABDOMINIS MUSCLES - V. A. Bondarev; V. A. Zurnadzhjants; M. A. Topchiev (Медицинский вестник Юга России, 2014)
Purpose: to improve the results of surgical treatment for diastasis of rectus abdominis muscles.Materials and methods: there were observed 2 groups of patients: the first one - 68 patients with diastasis of rectus abdominis muscles of 1-2 degrees and the second one – 9 patients with diastasis of rectus abdominis muscles of 2-3 degrees, aged of 40-65 years who received 2 ways of correction in diastasis of rectus abdominis muscles.Results: in the first group of patients there were observed the formation of seroma in one case and hematoma in two cases during early postoperative period. Recurrence of the disease was registered in one patient in 3 years after surgical interventions. In the second group there were no any complications and relapses during one year after operations.Summary: the surgical treatment of diastasis of rectus abdominis muscles by restoration of white abdominal line is one of the important questions of contemporary herniology.